Investigation of the nuclear matter distribution of 56Ni by elastic proton scattering in inverse kinematics. (26th November 2015) - Schmid, M von; Bagchi, S; Bönig, S; Csatlós, M; Dillmann, I; Dimopoulou, C; Egelhof, P; Eremin, V; Furuno, T; Geissel, H; Gernhäuser, R; Harakeh, M N; et al.
Abstract: We have measured the nuclear-matter distribution of the doubly-magic N = Z nucleus 56 Ni by investigating elastic proton scattering in inverse kinematics. The radioactive beam of 56 Ni was injected and stored in the experimental storage ring (ESR, GSI) and interacted with an internal hydrogen gas-jet target. The high revolution frequency of the ions in the ring enabled a high luminosity, despite the low density of the target being used. This way, measurements at very low momentum transfers became possible. By measuring the energy and the scattering angle of the recoiling protons, we were able to separate the elastic reaction channel from inelastic scattering to the first excited state of 56 Ni and deduced the differential cross section of 56 Ni Ni. The data were analyzed within the framework of the Glauber multiple-scattering theory in order to extract the nuclear-matter radius and radial matter distribution of 56 Ni. Parameterizing the matter distribution with the phenomenological Symmetrized Fermi distribution, a preliminary value of 3.5 fm for the rms matter radius was deduced. This experiment was part of an EXL (EXotic nuclei studied in Light-ion induced reactions at storage rings) campaign at GSI in 2012 and was the first successful investigation of nuclear reactions with a stored radioactive beam ever.